Clinical characteristics of patients with coronary artery disease by smoking status - Olga V. Nakhratova; Daria P. Tsygankova; Joseph M. Tsenter; Evgeny D. Bazdyrev (КардиоСоматика)
BACKGROUND: Many people worldwide use different tobacco products. Currently, most studies of smoking in various populations are focused on determining relationships, including the number of cigarettes smoked per day, pack/year and smoking indexes. Some studies evaluate important characteristics, such as the degree of nicotine dependence, type of smoking behavior, and level of motivation to quit smoking. This fact highlights this study relevance of a comprehensive assessment of smoking status.